Asymmetric Synthesis of 2H‐Azirines with a Tetrasubstituted Stereocenter by Enantioselective Ring Contraction of Isoxazoles. (12th December 2017) - Okamoto, Kazuhiro; Nanya, Atsushi; Eguchi, Akira; Ohe, Kouichi
Abstract: Highly strained 2 H ‐azirines with a tetrasubstituted stereocenter were synthesized by the enantioselective isomerization of isoxazoles with a chiral diene–rhodium catalyst system. The effect of ligands and the coordination behavior support the proposed catalytic cycle in which the coordination site is fixed in favor of efficient enantiodiscrimination by a bulky substituent of the ligand. In silico studies also support the existence of a rhodium–imido complex as a key intermediate for enantiodiscrimination.